Addressing transition to motherhood, guideline adherence by midwives in prenatal booking visits: Findings from video recordings. (February 2019) - Tichelman, Elke; Peters, Lilian; Oost, Jorien; Westerhout, Anne; Schellevis, François G.; Burger, Huibert; Noordman, Janneke; Berger, Marjolein Y.; Martin, Linda
Abstract: Objective: To assess if and how primary care midwives adhere to the guideline by addressing transition to motherhood at the first prenatal booking visit and to what extent there was a difference in addressing transition to motherhood between nulliparous and multiparous women. Design: Cross-sectional observational study of video-recorded prenatal booking visits. Setting and participants: 126 video recordings of prenatal booking visits with 18 primary care midwives in the Netherlands taking place between August 2010 and April 2011. Measurements: Five observers assessed dichotomously if midwives addressed seven topics of transition to motherhood according to the Dutch guideline prenatal midwifery care from the Royal Dutch Organization of Midwives and used six communication techniques. Frequencies and percentages of addressing each topic and communication technique were calculated. Differences between nulliparous and multiparous women were examined with Chi-Square tests or Fischer Exact tests, were appropriate. The agreement between the five observers was quantified using Fleiss' Kappa. Findings: During all visits at least one of the seven topics of transition to motherhood was addressed. The topics mother-to-infant bonding and support were addressed respectively in 2% and 16% of the visits. In almost all visits the topics desirability of the pregnancy, experience with the ultrasound examination or abdominal palpation or hearing the foetal heartbeat and practical preparation were addressed. Open questions for addressing transition to motherhood were used in 6% of the prenatal booking visits. Dutch midwives addressed transition to motherhood mostly by giving information (100%) and by using closed-ended questions (94%) and following woman's initiative (90%). Nulliparous women brought up transition to motherhood on their own initiative more often than multiparous women (97% versus 84%). For the topics 'desirability of the pregnancy 'and' practical preparations' and for conversation techniques 'giving information' and 'closed-ended questions', 100% agreement was achieved. However, the topic 'Support' had poor agreement (kappa = 0.19). Key conclusions and implications for practice: Although during every visit the transition of motherhood was addressed, the topics mother-to-infant bonding and support should get more attention. Midwives should improve adherence to the guideline by addressing transition to motherhood and by using more open questions. Furthermore, they should focus on taking the initiative to address the transition to motherhood in multiparous women themselves.